Analisis Produktivitas dan Daya Saing UMKM Cemilan Mahiru - Edo Bagus Prasetyo; Rika Wulandari; Marwan; Teguh Arifianto; Lusiana (Faculty of Economics and Business, University of Pancasakti Tegal, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the national economy, yet they continue to face challenges in productivity and competitiveness, particularly in the local bakery sector. This study aims to analyze the strategic position of Cemilan Mahiru, a bakery MSME in Sungai Penuh, Kerinci, and to formulate appropriate development strategies. The research employed a descriptive qualitative approach supported by quantitative analysis using the Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrices. Data were collected through interviews, observations, questionnaires, and literature review, and validated through triangulation techniques. The findings show that Cemilan Mahiru obtained an IFE score of 2.25 and an EFE score of 2.65, placing the business in Quadrant V of the IE matrix with a Hold and Maintain strategy. This position indicates that the enterprise should prioritize maintaining its existing market, improving internal efficiency, and gradually leveraging external opportunities. Recommended strategies include adopting simple digital marketing, limited product diversification, strengthening partnerships with suppliers, and utilizing government support programs. The study concludes that the development of micro-scale MSMEs should be directed toward gradual strategies aligned with internal conditions to achieve sustainable competitiveness